2008
DOI: 10.1038/ng.214
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for two independent prostate cancer risk–associated loci in the HNF1B gene at 17q12

Abstract: A fine mapping study in the HNF1B gene at 17q12 among two study populations revealed a second prostate cancer locus, ~26 kb centromeric to the first known locus (rs4430796); these are separated by a recombination hotspot. A SNP in the second locus (rs11649743) was confirmed in five additional populations, and P=1.7×10−9 for an allelic test in the seven combined studies. The association at each SNP remains significant after adjusting for the other SNP.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
131
1
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 150 publications
(137 citation statements)
references
References 17 publications
4
131
1
1
Order By: Relevance
“…Our finding differs from the two dozen PCa risk-associated SNPs discovered to date from GWAS (6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25). Although the associations for some SNPs, such as those at 8q24, were stronger among patients with aggressive PCa in some studies when each type of case is compared versus unaffected controls (35,36), these SNPs were not associated with PCa aggressiveness in any of the studies when patients with more or less aggressive PCa were directly compared.…”
Section: Discussioncontrasting
confidence: 54%
See 1 more Smart Citation
“…Our finding differs from the two dozen PCa risk-associated SNPs discovered to date from GWAS (6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25). Although the associations for some SNPs, such as those at 8q24, were stronger among patients with aggressive PCa in some studies when each type of case is compared versus unaffected controls (35,36), these SNPs were not associated with PCa aggressiveness in any of the studies when patients with more or less aggressive PCa were directly compared.…”
Section: Discussioncontrasting
confidence: 54%
“…Recent breakthroughs in genome-wide association studies (GWAS) have led to the discovery of more than two dozen reported SNPs that are associated with PCa risk by comparing men with or without PCa using case-control study designs (6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25). Unfortunately, none of these PCa risk-associated SNPs consistently distinguish risk for more or less aggressive cancer (26)(27)(28), nor are they associated with prostate cancer-specific mortality (29).…”
mentioning
confidence: 99%
“…[4][5][6] PCa is one of the common cancers with a large genetic component, as up to 42% of the risk could be explained by inheritance from studies about twins. 7 Genome-wide association studies (GWAs) have identified 46 susceptibility loci associated with PCa [8][9][10][11][12][13][14][15][16][17][18][19][20] that individually contribute to a small increase in PCa risk, but which taken together, could explain more than 25% of the excess of PCa familial risk. 13 Although present in only 1%-2% of sporadic PCa cases [21][22][23] germline mutations in the breast cancer predisposition gene 2 (BRCA2) are the genetic events known to date that confer the highest risk of PCa (8.6-fold in men f65 years).…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have also identified numerous SNPs in the HNF1B gene as being associated with the risk of cancers of the ovary and prostate glands (Kao et al, 2012;Chornokur et al, 2013), indicating that genetic variation in HNF1B might play an important role in the etiology of numerous cancers. Genomewide association studies have reported the HNF1B rs4430796 (A>G) polymorphism to be associated with a risk of prostate cancer (Gudmundsson et al, 2007;Sun et al, 2008;Liu et al, 2011;Zhou et al, 2011;Zhang et al, 2012;Chan et al, 2013;Rojas et al, 2014).…”
Section: Introductionmentioning
confidence: 99%